Do not attempt cardiopulmonary resuscitation (DNACPR) decisions in people admitted with suspected COVID-19: Secondary analysis of the PRIEST observational cohort study. (July 2021) - Sutton, Laura; Goodacre, Steve; Thomas, Ben; Connelly, Sarah
Abstract: Aims: We aimed to describe the characteristics and outcomes of adults admitted to hospital with suspected COVID-19 according to their DNACPR decisions, and identify factors associated with DNACPR decisions. Methods: We undertook a secondary analysis of 13, 977 adults admitted to hospital with suspected COVID-19 and included in the Pandemic Respiratory Infection Emergency System Triage (PRIEST) study. We recorded presenting characteristics and outcomes (death or organ support) up to 30 days. We categorised patients as early DNACPR (before or on the day of admission) or late/no DNACPR (no DNACPR or occurring after the day of admission). We undertook descriptive analysis comparing these groups and multivariable analysis to identify independent predictors of early DNACPR. Results: We excluded 1249 with missing DNACPR data, and identified 3929/12748 (31%) with an early DNACPR decision. They had higher mortality (40.7% v 13.1%) and lower use of any organ support (11.6% v 15.7%), but received a range of organ support interventions, with some being used at rates comparable to those with late or no DNACPR (e.g. non-invasive ventilation 4.4% v 3.5%). On multivariable analysis, older age (p < 0.001), active malignancy (p < 0.001), chronic lung disease (p < 0.001), limited performance status (p < 0.001), and abnormal physiological variables were associated with increased recording of early DNACPR. Asian ethnicity was associated with reduced recording of early DNACPR (p = 0.001). Conclusions: Early DNACPR decisions were associated with recognised predictors of adverse outcome, and were inversely associated with Asian ethnicity. Most people with an early DNACPR decision survived to 30 days and many received potentially life-saving interventions. Registration: ISRCTN registry, ISRCTN28342533, http://www.isrctn.com/ISRCTN28342533